Lithium chloride as a reference substance for urine collection in igoats - Schonewille, J.Th; Beynen, A.C. (New Zealand veterinary journal, 1999)
Lithium chloride is used as a compliance indicator in nutritional research with humans. At least 95% of ingested lithium is recovered in urine (Heijnen et al., 1996 ). Lithium may be added to foodstuffs in amounts much higher than those naturally occurring. The human subjects consuming those foodstuffs may be asked to collect their urine, and lithium determination can then serve to check dietary compliance. We speculated that lithium would be a suitable external urine marker in ruminants. Total urine collection from ruminants often is not feasible, and the possibility of calculating total urine production on the basis of lithium determination in a spot sample is attractive.